Innovations in foreign students language teaching - Vasetska, L.; Solovyova, O.; Васецька, Лариса Іванівна; Соловйова, Ольга Володимирівна (Liverpool : Cognum Publishing House, 2020)
The article analyzes the leading scientific theories on the topic, identifies the scientific sources of the development of the idea of interactive teaching of foreign languages in high school, presents the etymology of the names of interactive teaching methods, describes the essence of modern interactive teaching methods of Ukrainian as a foreign language with the presentation of scientific methods of teaching. The advantages of using modern methods and peculiarities of their introduction into the educational process are substantiated.
Keywords: active learning; game educational technologies; interactive training; innovative technologies; programmed training